Cutaneous fibroma in a common snapping turtle (Chelydra serpentina) - Thomeeran, H.; Selvarajah, Gayathri Thevi; Mazlan, Mazlina; Chong, Byron Y. L.; Law, H. L. (Veterinary Association of Malaysia (VAM), 2018)
This is a case report on the management of a common snapping turtle (Chelydra serpentina) with cutaneous fibroma which was managed surgically. An adult common snapping turtle was presented with a pink pendulous mass at the plantar of the left forelimb. The mass was pedunculated, pinkish-red in colour, round to oblong shape, 4 to 5 cm in diameter with central ulceration site. Microscopic examination revealed well-circumscribed and non-encapsulated mass in the dermal layer with stellate to spindle-shape cells dispersed throughout the tumour mass consist of collagen stroma. A diagnosis of cutaneous fibroma was made. In this case, the mass was removed surgically. Post-operatively, the turtle was managed with enrofloxacin antibiotics and carprofen as non-steroidal anti-inflammatory treatment. The snapping turtle recovered uneventfully.